2023
DOI: 10.1111/jora.12852
|View full text |Cite
|
Sign up to set email alerts
|

Relations between youths' community violence exposure and their physical aggression: The protective role of adults

Abstract: The purpose of this study was to examine whether adults moderated the relations between youths' community violence exposure and subsequent physical aggression. Participants were 2575 middle school students (Mage = 12.3, SD = 1.00; 52% female) in the southeastern U.S. who completed surveys collected in the fall, winter, spring, and summer. The sample was predominantly African American (72%). High adult support was associated with weaker relations between exposure to violence in the fall and aggression in the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Previous studies have found that perceived parental support for fighting is a risk factor (e.g., Kramer‐Kuhn & Farrell, 2016; O'Connor et al, 2020), and perceived parental support for nonviolence is a promotive factor (e.g., Coleman et al, 2023, based on longitudinal data from the current data set; Garthe et al, 2015) for aggression. In a predominantly Black sample of middle school students, Kramer‐Kuhn and Farrell (2016) found that adolescents' perceptions of parental messages supporting fighting were positively related to physical aggression in sixth and eighth graders, but not in seventh graders.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Previous studies have found that perceived parental support for fighting is a risk factor (e.g., Kramer‐Kuhn & Farrell, 2016; O'Connor et al, 2020), and perceived parental support for nonviolence is a promotive factor (e.g., Coleman et al, 2023, based on longitudinal data from the current data set; Garthe et al, 2015) for aggression. In a predominantly Black sample of middle school students, Kramer‐Kuhn and Farrell (2016) found that adolescents' perceptions of parental messages supporting fighting were positively related to physical aggression in sixth and eighth graders, but not in seventh graders.…”
Section: Introductionmentioning
confidence: 69%
“…The purpose of this study was to examine whether youths' beliefs about fighting mediated relations between perceived parental messages about fighting and nonviolence and subsequent changes in physical aggression. Although there is evidence that parental messages predict youths' aggression (e.g., Coleman et al, 2023), few studies have attempted to identify the underlying factors responsible for this relation. Overall, there was support for social norms theory, as reflected in a general pattern in which perceived parental messages about aggression predicted youths' beliefs about aggression, which predicted youths' physical aggression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations